Accountability Arrangements for Financial Sector Regulators - Hupkes, Eva (Economic Issues; Economic Issues ;, 2006)
Policymakers are often reluctant to grant independence to the agencies that regulate and supervise the financial sector because of the fear that these agencies, with their wide-ranging responsibilities and powers, could become a law unto themselves. This pamphlet describes mechanisms for making regulatory agencies accountable not only to the government but also to the industry they supervise and the public at large, with examples from a range of countries.